IL-4 peptide hydrogel reprograms MSC heterogeneity toward the CD106+ population for enhanced renal repair - Kai Pan; Enze Fu; Wenlong Wang; Rui Li; Jiansheng Yang; Hongyan Tao; Zhibo Han; Zhong-chao Han; Qiong Li; Zhikun Guo; Zongjin Li (Proceedings of the National Academy of Sciences, 2026)
Mesenchymal stem cells (MSCs) exhibit significant heterogeneity, which limits their therapeutic efficacy in regenerative medicine. Here, we introduce a self-assembled interleukin-4 (IL-4) peptide hydrogel designed to shift MSC populations toward a homogeneous CD106 + subset with enhanced regenerative and immunomodulatory capabilities. To evaluate their therapeutic potential, MSCs with the IL-4 hydrogel were administered to a murine model of acute kidney injury (AKI) via renal capsule transplantation. Compared with untreated MSCs, encapsulated MSCs exhibited superior engraftment and survival, leading to significant improvements in renal function, as evidenced by reduced serum creatinine levels, attenuated tubular necrosis, and decreased inflammatory infiltrates. These findings highlight the IL-4 peptide hydrogel as a promising platform for overcoming MSC heterogeneity and manufacturing disease-specific MSCs, offering a scalable strategy for advanced cell therapies in AKI and beyond.